Bio-coloration of bacterial cellulose assisted by immobilized laccase - Song, J. (2018)
In this work a process for the bio-coloration of bacterial cellulose (BC) membranes was developed. Laccase from Myceliophthora thermophila was immobilized onto BC membranes and retained up to 88% of residual activity after immobilization. Four compounds belonging to the flavonoids family were chosen to test the in situ polymerase activity of immobilized laccase. All the flavonoids were successfully polymerized by laccase giving rise to yellow, orange and dark brown oligomers which conferred color to the BC support. The optimal bio-coloration conditions were studied for two of the tested flavonoids, catechol and catechin, by varying the concentration and time of incubation. High color depth and resistance to washing were obtained for both compounds. The highly porous bacterial cellulose material demonstrated great performance as a bio-coloration support, in contrast to other materials cited in literature, like cotton or wool. The process developed is presented as an environmentally friendly alternative for bacterial cellulose bio-coloration and will contribute deeply for the development of new fashionable products within this material.